Joule heating estimation of photovoltaic module through cells temperature measurement - Erkata Yandri; Naoto Hagino (International Journal of Power Electronics and Drive Systems (IJPEDS), 2022)
Module temperature has a role in determining a PV module's performance. The purpose of this paper is to estimate the Joule heating in a photovoltaic (PV) module by comparing during PV-On (electricity generation) and PV-Off (without electricity generation). Joule heating was less evaluated due to simplifying formulation, which is easier to implement in experimental observation as proposed in this work. The experiment collected the temperature distributions of the PV module during PV-On and PV-Off. PV module temperature distribution follows the normal distribution curve as the irradiation uniformity pattern of the solar simulator has a slight ≤0.3 oC difference between PV-On and PV-Off. Joule heating slightly increased the PV module temperature by 0.53 K/A, proportional to the irradiances. Joule heating has increased almost seven times from 2.65 W at 700 W/m2 to 18.07 W at 1000 W/m2. Joule heating might slightly increase the overall thermal conductivity and slightly decrease the thermal resistances. It might affect the heat transfer. This research may improve the procedures prediction of PV or photovoltaic-thermal (PVT) collector temperature by considering Joule heating.